Electrically-Assisted Formation and Desorption of Dodecyl Phosphate Self-Assembled Monolayers on Indium Tin Oxide Surfaces - Tang, Clarence S.; Antoni, Mathieu; Schönbächler, Isabelle; Keller, Beat; Textor, Marcus; Voros, Janos (My University, 2005)
Molecularly homogenous and hydrophobic surfaces play an important role in a number of technological applications such as tribology and protein/cellular adhesion. Self-assembled monolayers of dodecyl phosphates (DDPO4) have previously been demonstrated to spontaneously form on titanium oxide, producing surfaces with excellent hydrophobic properties. In this paper, we report on the adsorption of DDPO4 onto a transparent electronic material, indium tin oxide (ITO), under both open circuit and applied potential conditions. We have used two complementary surface characterization techniques: variable angle scanning ellipsometry and contact angle measurements to investigate the adsorption of DDPO4 on an ITO surface. Under open circuit condition, both methods consistently confirmed the formation of DDPO4 monolayers on the ITO surface. The presence of an electrical field increased the amount of DDPO4 adsorbed on the ITO surface. An applied anodic electrical stimulus of 1800 mV resulted in an exponential loss of the monolayer as confirmed by X-ray photoelectron spectroscopy and electrochemical optical waveguide lightmode spectroscopy (EC-OWLS). This electrically stimulated selective adsorption/desorption of DDPO4 opens up new ways to tailor the physico-chemical properties of surfaces.